2009
DOI: 10.1111/j.1872-034x.2008.00380.x
|View full text |Cite
|
Sign up to set email alerts
|

Emodin reverses CCl4 induced hepatic cytochrome P450 (CYP) enzymatic and ultrastructural changes: The in vivo evidence

Abstract: By reversal CYP activity and ultrastructural changes, emodin shows a strong hepatoprotective abilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Lee et al demonstrated that emodin might be valuable for the protection of CCl 4 ‐induced liver injury by reducing lipid peroxidation and by positively modulating inflammation (Lee et al ., ). Emodin also had the ability to prevent CCl 4 ‐induced liver damage through reversing hepatic oxidative insults, CYP enzymatic activity and ultrastructural changes (Bhadauria et al ., ). In addition, emodin at a dose of 30 mg/kg (po) possessed optimum hepatoprotective ability against acetaminophen (APAP)‐induced toxicity via diminishing oxidative stress (Bhadauria, ).…”
Section: Pharmacologymentioning
confidence: 97%
“…Lee et al demonstrated that emodin might be valuable for the protection of CCl 4 ‐induced liver injury by reducing lipid peroxidation and by positively modulating inflammation (Lee et al ., ). Emodin also had the ability to prevent CCl 4 ‐induced liver damage through reversing hepatic oxidative insults, CYP enzymatic activity and ultrastructural changes (Bhadauria et al ., ). In addition, emodin at a dose of 30 mg/kg (po) possessed optimum hepatoprotective ability against acetaminophen (APAP)‐induced toxicity via diminishing oxidative stress (Bhadauria, ).…”
Section: Pharmacologymentioning
confidence: 97%
“…In addition, emodin and scopoletin are not P-gp substrates [ 45 , 46 ], so it would not be reduced because of the change of P-gp. Moreover emodin can also reverse CCl 4 -induced hepatic CYP enzymatic of hepatic drug-metabolizing enzymes [ 47 ], which could partly explain unchanged pharmacokinetic behavior. The causes and effects of the pharmacokinetic changes of components in YCHT still need further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…The histological observations in the present study were consistent with these previous results, which indicated the protective effect of Sal B on mice against the liver injury induced by CCl 4 ; 30 mg/kg Sal B had a strong protective effect on acute and chronic liver injury. Hepatocellular damage can be triggered by CCl 4 and the CYP450 enzyme system is predominantly responsible for the metabolism of CCl 4 to form free radicals (35). Highly reactive radicals generated from CCl 4 , such as trichloromethyl and trichloromethyl peroxyl, which destroy the respiratory chain on the mitochondrial membrane (36), then accumulate ROS in the cells to produce oxidative stress (37).…”
Section: Discussionmentioning
confidence: 99%